Improvement of Nurse Competence in Puskesmas In Handling Emergency Response to Cardiac arrest case for Reduce Mortality Rate In Pre Hospital Order Through Training Â Pulmonary Heart Resuscitation In Pangandaran District - Prawesti, Ayu; Emaliyawati, Etika; Trisyani, Yanny (Jurnal Keperawatan, 2018)
There are many cardiac arrest events in the community that can not be saved because they do not get the right and quick action due to the ignorance and the inability of the nurses of the puskesmas to provide emergency response to cardiac pulmonary resuscitation. Cardiopulmonary resuscitation (CPR) is the main action in cardiac arrest and stop breath, which can increase life expectation. Goal to be achieved in the implementation of this program is increased ability of nurse puskesmas in performing action of heart resuscitation of lung. The specific targets of the activities are the increased ability of health center nurses on the ability to perform cardiopulmonary resuscitation with the latest guidelines and the implementation of a structured training program on pulmonary cardiac resuscitation at community health center nurses on an ongoing basis. Solutions offered to overcome the problem is the training of Lung Heart Resuscitation (RJP) to nurses Puskesmas. Training activities conducted for one day include pre-test evaluation, material exposure, rjp skills training and post training evacuation. The result showed that there was significant difference between attitude value and perceived behavioral control between before and after training, whereas there was no difference of subjective norm value between before and after training. Training on updating and increasing the competence of cardiopulmonary resuscitation should be done regularly and periodically. Routine and periodic training needs to be done to improve nursing services, especially cardiovascular emergency